Vitamin C and total soluble solid content of crystal guava at different storage duration and ripeness - Khafid, Abdul; Nurchayati, Yulita; Hastuti, Endah Dwi; Setiari, Nintya (Universitas Padjadjaran, 2023)
Crystal guava (Psidium guajava var. 'Crystal') fruit is in great demand because of its delicious taste and high nutritional content. Storage aims to prevent postharvest damage to the fruit. However, storage that is too long causes morphological damage and decreased nutrients. This study aims to determine the effect of storage duration, fruit ripeness stage and the interaction between both factors on vitamin C and total soluble solids (TSS) content of crystal guava, and determine which treatment can produce the highest vitamin C and TSS. Fruits harvested simultaneously with three levels of ripeness based on the skin color: unripe fruit is dark green, ripe is light green, very ripe is yellowish green. Samples selected based on the same weight range. Storage was carried out for 0, 5, and 10 days at ± 10oC. The study used a completely randomized design (CRD) with a 3x3 factorial pattern with two factors: storage duration and fruit ripeness level. Parameters observed were vitamin C, TSS, weight loss, diameter shrinkage, skin color and hardness. Data were analyzed using ANOVA and DMRT. Both treatments showed an interaction on vitamin C content. The best treatment was unripe fruit stored for ten days with 14.955 ppm of vitamin C. Both treatments did not show any interaction on TSS content. The best treatment was five days storage with TSS of 8.25 °Brix and very ripe fruit of 8.21 °Brix. Based on vitamin C, TSS content, and physical condition variables, the best guava fruit is unripe fruit stored for 10 days.Keywords: color, postharvest, physical, quality, softening